A price comparison of recently launched proprietary pharmaceuticals in the UK and the US. Issue 1 (1st January 2016) - Jørgensen, Jesper; Kefalas, Panos
Abstract : Objective: To explore the relationship between prices charged by manufacturers of proprietary pharmaceuticals in the US and in the UK in recent years (2013–2016), expressed as a multiplier, and to detail to what extent this relationship differs for high-cost therapies used in smaller patient populations, as compared to lower-cost drugs. Methodology: Therapies assessed by the Scottish Medicines Consortium (SMC) in the UK between 1 January 2013 and 1 June 2016 were identified; only in-patent therapies were included in the analysis (to avoid the impact of price erosion post patent expiry); results were grouped according to annual cost per patient (whether considered high-cost, i.e., >£2, 500 per patient per year, or not) and the size of the UK target population [whether considered orphan (<32, 000 patients per year), ultra-orphan (<1, 000 patients per year), or not]. Publicly listed prices were obtained in the US and UK and were adjusted where necessary to estimate the prices charged by manufacturers in the respective countries. The difference in price (per unit of the same strength and formulation) was calculated as a multiplier between the US and UK prices for each of the therapies identified. Results: Based on the methodological approach described, 88 therapies were identified and included in the analysis. The multiplier between the US and UK prices was 3.64 for therapies with an estimated annual cost <£2, 500; this was reduced to 1.90 for higher-cost therapies. A downward trend was also evident in the subgroup analysis of the higher-cost therapies; as the estimated target patient populations reduced from >32, 000 down to <1, 000, the US/UK price multipliers reduced from 2.13 for the former to 1.48 for the latter. Conclusion: Although pharmaceutical prices have been found to be on average substantially higher in the US compared to the UK, our findings suggest that this price discrepancy is smaller for higher-cost therapies targeting small patient populations. Manufacturers of high-cost products should therefore factor this in when formulating pricing strategies because the potential for higher pricing in the US seems greater for primary care products targeting large patient populations.